1990
DOI: 10.1093/oxfordjournals.jbchem.a123024
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure of a Fucose-Specific Lectin Obtained from a Mushroom, Aleuria aurantia

Abstract: Aleuria aurantia lectin (AAL) is a protein composed of two identical subunits having no carbohydrate chain and shows sugar-binding specificity for L-fucose. Full-length cDNA encoding for the lectin has been isolated from a lambda gt11 library, screened with an antiserum directed against AAL. The cDNA clone contained 1,370 nucleotides and an open reading frame of 939 nucleotides encoding 313 amino acids. The amino-terminal sequence (residues 1-30) of the lectin isolated from the mushroom coincided with the dedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 0 publications
1
50
0
Order By: Relevance
“…Homodimer 4 Gal na Entomotoxic (Hamshou et al 2013;Hamshou et al 2010b;Hamshou et al 2012;Skamnaki et al 2013) Bleuler-Martinez et al 2011;Fujihashi et al 2003;Fukumori et al 1990;Kochibe and Furukawa 1980;Olausson et al 2010;Olausson et al 2008;Tateno et al 2009;Wimmerova et al 2003) GlcNAc-β1,4-X na nd (Cioci et al 2006;Ueda et al 1999a;Ueda et al 2002;Ueda et al 1999b;Ueda et al 2003) Entomotoxic (Birck et al 2004;Bleuler-Martinez et al 2011;Damian et al 2005;Francis et al 2003;Jaber et al 2008;Jaber et al 2007;…”
Section: β-Trefoilmentioning
confidence: 99%
“…Homodimer 4 Gal na Entomotoxic (Hamshou et al 2013;Hamshou et al 2010b;Hamshou et al 2012;Skamnaki et al 2013) Bleuler-Martinez et al 2011;Fujihashi et al 2003;Fukumori et al 1990;Kochibe and Furukawa 1980;Olausson et al 2010;Olausson et al 2008;Tateno et al 2009;Wimmerova et al 2003) GlcNAc-β1,4-X na nd (Cioci et al 2006;Ueda et al 1999a;Ueda et al 2002;Ueda et al 1999b;Ueda et al 2003) Entomotoxic (Birck et al 2004;Bleuler-Martinez et al 2011;Damian et al 2005;Francis et al 2003;Jaber et al 2008;Jaber et al 2007;…”
Section: β-Trefoilmentioning
confidence: 99%
“…By contrast, LCA appeared as two bands corresponding to molecular weights of 6000 and 18,000. Previous studies have reported the molecular weight of AAL as 66,796, consisting of identical subunits of 33,398 (15), and that of LCA as 46,000, consisting of four subunits (␣ 2 ␤ 2 ): two of 5,710 and two of 17,572 (24). In SPR analysis, HCl injection (100 mM, 100 l) into a CM5 sensor chip flow cell immobilized with purified AOL resulted in a decrease in resonance units (RU), corresponding to approximately half the amount of immobilized ligand (data not shown), which suggests that AOL consists of two identical subunits.…”
Section: Preparation and Protein Characteristics Of Aol-mentioning
confidence: 99%
“…Among these lectins, AAL and R. stolonifer lectin preferentially bind to ␣1,6-fucosylated oligosaccharides, whereas Ulex europaeus and Lotus tetragonolobus lectins prefer ␣1,2-linked fucose residues (14). AAL is a commercially available lectin that is known for its high affinity for ␣1,6-fucosylated oligosaccharides (15), and it is widely used to estimate the * The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C.…”
mentioning
confidence: 99%
“…Immunoblotting was performed as reported. 8) Hemagglutination assay. The hemagglutinating activity of purified His-tag-AAL was assayed as reported.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] The primary structure of AAL consists of 312 amino acids having six internal homologous regions. 7,8) AAL has been reported to be a dimer of identical monovalent subunits.…”
mentioning
confidence: 99%